The relationship between metabolite from 1H-MRS and brain volume by magnetic resonance technique in methamphetamine users - Intachai, Nuttawadee; Rodkong, Artit; Sailasuta, Napapon; Aramrattana, Apinun; Uttawichai, Kanok; Thompson, Mekkla; Sirirojn, Bangorn; Thavornprasit, Daralak; Taejaroenkul, Sineenart; sintupat, Kamolrawee; Valcour, Victor; Paul, Robert; et al. (Journal of Associated Medical Sciences, 2017)
Background: Methamphetamine (MA) is a highly addictive stimulant causes neurotoxicity. Changes of brain metabolites and brain volumes in MA abusers have been documented. However, the relationship between changes of brain metabolites at a selected brain location and changes of brain volumes at the same location has never been reported. Objectives: To explore the relationship between brain metabolites and brain volumes from the same locations in MA users. Materials and methods: Ten MA users and 14 Healthy control (HC). For the brain volumes, T1-weighted high resolution images were acquired using 3D FFE pulse sequence. FreeSurfer version 5.3 was applied for brain volumes analysis. Single voxel MRS was acquired in 4 voxel locations and using PRESS pulse sequence for scanning. TARQUIN version 4.3.5 was applied for brain metabolites. Pearson correlations was used to analyze the correlation between brain metabolites and brain volumes in MA users. Results: MA users showed significantly reduced NAA (p=0.023) and NAA/Cho (p=0.05) in left FWM, compared with HC group. In left BG region, MA user group showed significantly reduced NAA/Cho (p=0.042) and increased Cho (p=0.05), compared with HC group. MA user group showed significantly reduced FGM volume (p=0.043). For the analysis of relationship between metabolites and brain volume, it was found that there are significant correlations between reducing of NAA at FGM region and FGM volume (n=10, r=0.635, p=0.049), and significant negative correlations between reducing of Cr at PGM region and OGM volume (n=10, r= -0.741, p=0.022). Conclusion: Significant correlations between brain metabolites and brain volumes at FGM and PGM regions.